Transformasi Limbah Organik menjadi Produk Bernilai Ekonomi: Pemberdayaan Ibu-Ibu Aisyiyah Cabang Tikung melalui Pelatihan Eco-Enzyme - Sri Yaumi; Rita Nataliawati; Qosim; Mesra Berlyn Hakim; Abdul Majid (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
Household organic waste management remains a challenge because most organic waste is not utilized productively. This community service program aimed to improve the understanding and skills of Aisyiyah women in the Tikung Branch regarding the processing of organic waste into eco-enzyme. The activity was conducted over two days at Rumah Eco-Enzyme Kranji, Paciran, involving 32 participants. The program employed a participatory training approach through lectures, demonstrations, group practice, discussions, and reflections. Evaluation was conducted through direct observation, documentation, and informal interviews. The results showed that 29 participants were able to identify the main ingredients of eco-enzyme, 28 participants understood the production process, 27 participants recognized the fermentation period, and 30 participants understood the benefits of eco-enzyme for household and environmental purposes. All participants actively engaged in the practical sessions, and each group successfully produced an initial eco-enzyme fermentation solution. The program successfully increased participants’ knowledge, basic skills, and commitment to implementing household organic waste management practices.